International Accounting Standardization Effects on Business Management: Evidence from Hungary (Global Journal of Management and Business Research, 2011)
This paper traces the benefits of international accounting standards and their contribution to harmonization in business practice. In this review, the goal is to describe and summarize how the accounting standards promote management decisions and influence the business environment in a global scale. It is expected that the unified, standardized accounting information system will lead to new types of analysis and data, furthermore with the possible integration of new indicators from the business management practice of certain countries.In the scientific research methodology the author assigned that the Balance Sheet indexes deteriorated especially regarding solvency and prosperity after adaptation of IFRS. Earnings management reduced after the post-adoption period.